Teacher’s Strategies in Students’ Character Development in the New Normal Era of Rural Area in South Sulawesi - H. Syamsuni HR; Nur Syamsiah; Muh Indra Budiman (AL-ISHLAH: Jurnal Pendidikan, 2022)
COVID-19 pandemic has had the biggest impact on human life, including education. During COVID-19 pandemic, learning is done online in the schools, so the teachers and children/students are longer meet face to face for approximately two years. The learning process is carried out at home, it can change the character of the students. This study aims to describe the teacher's strategy in developing the characteristics of students and to explore the characteristics of students in the new normal era of rural areas in South Sulawesi. The type of research used qualitative research using three data collection techniques, namely interviews, observation and documentation of 10 teachers, and 10 school committees. Data had been collected and analyzed textually. The teacher's strategy in developing the character of students in rural areas during the new normal had no difference with the character development of students before the COVID-19 pandemic. It's just that in this new normal, teachers were more intense and more assertive in implementing strategies in the context of character development that had been going on for a long time. The teacher strategy was the application of instructional objectives, building communication and cooperation with parents, integration of character education with other subjects, and cultural transfer.